Prediction of the Effect of Sleep Deprivation on Response Inhibition via Machine Learning on Structural Magnetic Resonance Imaging Data - Zhao, Rui; Zhang, Xinxin; Zhu, Yuanqiang; Fei, Ningbo; Sun, Jinbo; Liu, Peng; Yang, Xuejuan; Qin, Wei (Frontiers in Human Neuroscience, 2018)
Sleep deprivation (SD) impairs the ability of response inhibition. However, few studies have explored the quantitative prediction of performance impairment using magnetic resonance imaging (MRI) data. In this study, structural MRI data were used to predict the change in response inhibition performance (△SSRT) measured by a stop-signal task after 24 hours of SD in 52 normal young subjects. For each subject, T1-weighted MRI data were acquired and the gray matter (GM) volumes were calculated using voxel-based morphometry analysis. First, the regions in which GM volumes correlated with △SSRT were explored. Then, features were extracted from these regions and the prediction process was performed using a linear regression model with four-fold cross-validation. We found that the GM volumes of the left middle frontal gyrus, pars opercularis of right inferior frontal gyrus, pars triangularis of left inferior frontal gyrus, pars opercularis of right rolandic area, left supplementary motor area, left hippocampus, right lingual gyrus, right postcentral gyrus and left middle temporal gyrus could predict the △SSRT with a low mean square error of 0.0039 ± 0.0011 and a high Pearson’s correlation coefficient between the predicted and actual values of 0.948 ± 0.0503. In conclusion, our results demonstrated that a linear combination of structural MRI data could accurately predict the change in response inhibition performance after SD. Further studies with larger sample sizes and more comprehensive sample may be necessary to validate these findings.